Increased drought reduces acorn production in Quercus ilex coppices: thinning mitigates this effect but only in the short term - Sánchez-Humanes, Belén; Espelta, Josep Maria (Forestry, 2011)
In order to explore the effects of climate change on Mediterranean regenerating forests, we experimentally assessed the effects of increased drought on the reproductive attributes of Quercus ilex over a 4-year period (2005–2008). We also investigated whether traditional thinning (selection of one to a few stems per stump) could mitigate the consequences of increased drought in oak coppices. Increased drought reduced the number of reproductive trees, mean number of female flowers produced and acorn crop size, although most of these effects appeared only in the last 2 years of the experiment. In a different way, thinning enhanced all reproductive attributes, but its main effects were transient and covered only 1 or 2 years after the application of the treatments. Our results indicate that a moderate reduction in rainfall (15 per cent) reduces the reproductive ability of Q. ilex. This may have long-term negative consequences for recruitment as well as for the fauna feeding on acorns. Although traditional thinning may mitigate the consequences of increased drought, it has a remarkably short-term effect. This highlights the need to re-examine traditional forestry practices as potential adaptive strategies for coping with climate change in Mediterranean regenerating forests.
10.1093/forestry/cpq04510.1093/forestry/cpq045
Keywords: acorn production; Drought; Mediterranean forest (voyant); Quercus ilex; thinning

Long-term CO 2-enrichment in a Mediterranean natural forest: An application of large Open Top Chambers - Angelis, P. De; Scarascia-Mugnozza, G. E. (Chemosphere, 1998)
It is crucial to be able to anticipate the possible effects of environmental changes on the Mediterranean woodland communities given their essential role on protecting lands that are under a strong pressure by man and climate. Predictions of the effects of increasing C0~ concentration on plants have been inferred by short- and long-term studies, conducted at different scales and by different technologies. Open Top Chambers (OTCs) are experimental facilities that have been widely used to expose field grown plants to different pollutant gases, and more recently to elevated [CO2] . In this paper, we present the natural site and the experimental system (six large OTCs enclosing clumps of natural vegetation) that we have been utilizing for 3 years, to assess the impact of elevated [CO2] on a Mediterranean natural forest community. The results show that large OTCs can be usefully used to simulate C02 doubling even under the harsh environmental conditions of the mediteffanean region
Keywords: decomposition; Elevated CO3; leaf litter; Mediterranean forest (voyant)